THE ROLE OF MUSLIM WOMEN IN GLOBAL ECONOMIC DYNAMICS - Rati Purnama Sari; Khairun Naziha Batubara; Khairani Hayat Situmorang (CV. Barokah Publsiher, 2026)
This study examines the role of Muslim women in global economic dynamics by integrating perspectives of gender, economic participation, and Islamic values. The research addresses the problem of limited participation of Muslim women in the global economy despite their significant potential. Using a qualitative approach with a literature review method, this study analyzes data from reputable books, academic journals, and international institutional reports. The findings indicate that Muslim women contribute significantly to economic development through labor participation, entrepreneurship, and informal sectors. However, their role is influenced by empowerment factors such as access to education, economic resources, and decision-making capacity. In addition, structural and socio-cultural barriers, including limited opportunities and interpretations of religious values, continue to affect their participation. The study also finds that Islamic values, when interpreted contextually, can support rather than hinder women's economic involvement. This research highlights that empowering Muslim women can enhance economic growth and social welfare. Therefore, inclusive policies, improved access to education and financial resources, and contextual understanding of Islamic values are essential to optimize the role of Muslim women in the global economy.